Intraoperative Cognitive Mapping Tasks for Direct Electrical Stimulation in Clinical and Neuroscientific Contexts - Bu, Linghao; Lu, Junfeng; Zhang, Jie; Wu, Jinsong (Frontiers in Human Neuroscience, 2021)
Direct electrical stimulation (DES) has been widely applied in both guidance of lesion resection and scientific research, however the design and selection of intraoperative cognitive mapping tasks have not been updated in a very long time. We introduce updated mapping tasks for language and non -language functions, and provide recommendations for optimal design and selection of intraoperative mapping tasks. In addition, with DES becoming more critical in current neuroscientific research, a task design that has not been widely-used in DES yet (subtraction and conjunction paradigms) was introduced for more delicate mapping of brain functions especially for research purposes. We also illustrate the importance of designing a common task series for DES and other non-invasive mapping techniques. This review gives practical updated guidelines for advanced application of DES in clinical and neuroscientific research.